Advanced Fan Controller Using Atmega 1284P - Apostol, F G; Predusca, G (The scientific bulletin of Electrical Engineering Faculty, 2018)
The project aims at creating a monitoring and control circuit in a desktop or complex system with the possibility to set the operating parameters. The project allows automatic and manual control of a certain number of fans using Pulse Width Modulation (PWM) control by the user or automatically by the system monitoring thresholds of minimum and average temperatures (also set by the user within the code). The system was designed with the following options: audible and visual alert when reaching maximum temperatures; time display, PWM percentage and three temperatures shown on a 16x2 LCD; the system-acquired data is then transmitted to a website. Additional features include the possibility of setting a color inside the system, also used as an alert as well as a color adjustment function by sound (for a musical lightshow). The mode of operation is based on the source code written in the Arduino IDE 1.6.3 software with the help of free libraries and free codes provided on the internet.